(untitled) (Mantichora. Italian Journal of Performance Studies, 2025)
The effects of human influence on the earth have ushered a new era, the Anthropocene, even causing a paroxysmal surge in the ecological imagination of popular media. Indeed, ecology is not only a social, political and scientific issue, but also a topic of cultural criticism. Our daily lives are so full of precarious and contradictory information about the world we live in, that it generates widespread uncertainty, especially about the most serious issues such as climate change. This article reminds us that literature, as a relational, empathetic and performative tool, has the opportunity to creatively and actively address such concerns, problematizing, reformulating and re-imagining them, to open new paths to our ecological thinking. Above all, the idea that nature is not a cultural product, but rather a process of uninterrupted exchange between the human and the other non-human, of relationships between opposites within a given environment, the biosphere. And it is through language and speech that this process can become socially and ethically reflective and politically aware. A particular type of word, however, capable of arousing fear, or rather its paradox, because catastrophe reveals the worst and best of man.